An isolated cuboid dislocation. A case report. (2017) - Sheahan, K.; Pomeroy, E.; Bayer, T.
Highlights: Isolated cuboid dislocations are rare injuries. Case reports are scarce in the literature. Closed reduction is difficult. Open reduction and internal fixation is usually necessary. The mechanism of injury is an inversion and plantar flexion type injury. Abstract: Introduction: Isolated cuboid dislocations are rare injuries Jacobson (1990). It is clinically significant and important in surgical education, as it is an injury and a source of lateral foot pain that can be misdiagnosed at the time of initial presentation and may be difficult to identify clinically or with imaging Drummond and Hastings (1969). Presentation of case: We present a case report in a 33 year old rugby player, who was injured during a match after a tackle. The patient had ongoing concerns that he was not recovering following initial discharge, as he was unable to weight bear since his initial presentation to the Emergency Department (E.D.), and he had ongoing lateral foot pain. Discussion: Important clinical findings include lateral foot pain, a palpable gap at the cuboid level and difficulty weight-bearing. Closed reduction is usually difficult as it can be blocked mechanically by the extensor digitorum brevis muscle or peroneus longus tendon Dobbs et al. (1969). Initial X-Rays may be inconclusive with this presentation. CT scanning is indicated if suspicion for pathology is high. Open reduction and internal fixation with Kirschner wires are usually necessary for isolated cuboid dislocations. Conclusion: Our take home message from this case report is that cuboid dislocations are rare injuries and are important to be aware of in reviewing X-rays in the E.D. Particularly in patients with inversion and plantar flexion type injuries to their foot and ankle joint, with an inability to weight bear and lateral midfoot pain following their injury.